The success of the Tagal system: a sustainable community-based riverine fisheries resource management in Sabah - Jephrin, Zefrinus Wong (Sabah Forestry Department, 2014)
The Tanjung Aru island is part of the Elopura Forest Reserve, classified as a mangrove forest reserve. It is located across the sea, opposite Sandakan town. The main village is Kg. Tanjung Aru, located at the northwestern part of the island at the estuary of Sg. Tg. Aru. Due to its proximity to Sandakan and the recent declaration of Sandakan as a nature city, the island has potentials in nature tourism. Based on preliminary surveys, this paper highlights some of the tourism potentials in Tg. Aru island and also the problems and recommendations in promoting tourism.